Anti-Leishmania activity and molecular docking of unusual flavonoids-rich fraction from Arrabidaea brachypoda (Bignoniaceae) - das Neves, Monica A.; do Nascimento, Jessyane R. [UNESP]; Maciel-Silva, Vera Lucia; dos Santos, Alberto M.; Junior, Jaldyr de Jesus G.V.; Coelho, Ana Jessica S.; Lima, Mayara Ingrid S.; Pereira, Silma Regina F.; da Rocha, Cláudia Q. (Elsevier, 2024)
Leishmaniases comprise a group of infectious parasitic diseases caused by various species of Leishmania and are considered a significant public health problem worldwide. Only a few medications, including miltefosine, amphotericin B, and meglumine antimonate, are used in current therapy. These medications are associated with severe side effects, low efficacy, high cost, and the need for hospital support. Additionally, there have been occurrences of drug resistance. Additionally, only a limited number of drugs, such as meglumine antimonate, amphotericin B, and miltefosine, are available, all of which are associated with severe side effects. In this context, the need for new effective drugs with fewer adverse effects is evident. Therefore, this study investigated the anti-Leishmania activity of a dichloromethane fraction (DCMF) extracted from Arrabidaea brachypoda roots. This fraction inhibited the viability of L. infantum, L. braziliensis, and L. Mexicana promastigotes, with IC50 values of 10.13, 11.44, and 11.16 µg/mL, respectively, and against L. infantum amastigotes (IC50 = 4.81 µg/mL). Moreover, the DCMF exhibited moderate cytotoxicity (CC50 = 25.15) towards RAW264.7 macrophages, with a selectivity index (SI) of 5.2. Notably, the DCMF caused damage to the macrophage genome only at 40 µg/mL, which is greater than the IC50 found for all Leishmania species. The results suggest that DCMF demonstrates similar antileishmanial effectiveness to isolated brachydin B, without causing genotoxic effects on mammalian cells. This finding is crucial because the isolation of the compounds relies on several steps and is very costly while obtaining the DCMF fraction is a simple and cost-effective process. Furthermore, In addition, the potential mechanisms of action of brachydins were also investigated. The computational analysis indicates that brachydin compounds bind to the Triosephosphate isomerase (TIM) enzyme via two main mechanisms: destabilizing the interface between the homodimers and interacting with catalytic residues situated at the site of binding. Based on all the results, DCMF exhibits promise as a therapeutic agent for leishmaniasis due to its significantly reduced toxicity in comparison to the adverse effects associated with current reference treatments.
Keywords: Cytotoxicity; Dimeric flavonoids; Genotoxicity; Leishmaniases; Molecular docking